1987
DOI: 10.1111/j.1570-7458.1987.tb00550.x
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of larval Colorado potato beetle growth and development by digestive proteinase inhibitors

Abstract: Evidence is presented that the Colorado potato beetle (CPB) (Leptinotarsa decemlineata (Say)) depends, at least partially, on cysteine proteinases for protein digestion. Midgut homogenates of CPB larvae have a mildly acidic pH and exhibit major proteolytic activity in the mildly acidic pH range. This proteolytic activity is activated by reducing agents, is inhibited by E‐64 (a specific cysteine proteinase inhibitor), and is not inhibited by serine proteinase inhibitors. In addition, consumption of E‐64 treated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
55
0
5

Year Published

1997
1997
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(61 citation statements)
references
References 13 publications
0
55
0
5
Order By: Relevance
“…Although no chemical tests were performed, results from studies on other solanaceous plants suggest that damage-induced chemicals may play a role in determining performance and preference in horsenettle. For instance, studies on potatoes, tomatoes, and tobacco have shown that herbivore damage can induce proteinase inhibitors and alkaloids that deter subsequent feeding and slow larval growth of even specialist insects like the Colorado potato beetle Leptinotarsa decemlineata (Green & Ryan, 1972;Roddick, 1986;Wolfson & Murdock, 1987;Baldwin, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…Although no chemical tests were performed, results from studies on other solanaceous plants suggest that damage-induced chemicals may play a role in determining performance and preference in horsenettle. For instance, studies on potatoes, tomatoes, and tobacco have shown that herbivore damage can induce proteinase inhibitors and alkaloids that deter subsequent feeding and slow larval growth of even specialist insects like the Colorado potato beetle Leptinotarsa decemlineata (Green & Ryan, 1972;Roddick, 1986;Wolfson & Murdock, 1987;Baldwin, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…Before finding APs in some insects like Coleoptera, it was proven that pepstatin, a powerful and specific inhibitor of APs, strongly inhibited proteolysis of the midgut enzymes of Colorado potato beetle, L. decemlineata, demonstrating that an AP was present in the midgut extracts (Wolfson and Murdock, 1987). In corn, cysteine protease has been shown to confer resistance to fall armyworm (Spodoptera frugiperda) via degradation of the peritrophic membrane of this chewing insect, which interferes with nutrient acquisition, ultimately killing the insect (Jiang et al, 1995;Pechan et al, 2002;Mohan et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…1978) pokazao je značajnu inhibiciju rasta larvi krompirove zlatice (Wolfson & Murdock, 1987;Bolter & Latoszek-Green, 1997), kao i toksični efekat tokom razvića larvi drugih koleoptera (Murdock i sar. 1988;Oppert i sar.…”
Section: Biotest Sa Larvama Krompirove Zlatice (Leptinotarsa Decemlinunclassified
“…Poznato je da krompirova zlatica digestivnu proteolizu bazira na cisteinskim i aspartatnim proteinazama (Wolfson & Murdock, 1987;Thie & Houseman, 1990; Michaud i sar. 1993) ali detektovana je i minorna digestivna aktivnost sa karakteristikama serinskih i metalo proteinaza (Novillo i sar.…”
Section: Analiza Digestivnih Proteinazaunclassified
See 1 more Smart Citation